Interior Rumah Tinggal Berbasis CPTED Sebagai Upaya Preventif Mencegah Kriminalisasi di Surakarta : The Application of CPTED in Residential Interiors as a Preventive Measure Against Criminalization in Surakarta - Budiwiyanto, Joko; Badriyah, Siti; Prasetyo, Raden Ersnathan Budi; Adrianto, Aditya Eko (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Crime prevention in densely populated urban areas such as Jebres, Surakarta, presents a serious challenge that requires preventive solutions grounded in interior and environmental design. Crime Prevention Through Environmental Design (CPTED) offers a practical approach by leveraging physical interior design to minimize opportunities for criminal activity. This community service project aimed to implement fundamental CPTED principles within residential interiors as a preventive strategy against crime in densely inhabited neighborhoods. The partners in this initiative were residents of Jebres, Surakarta, a densely populated urban community vulnerable to security threats. The methodology combined education, design simulation, and case-based mentoring applied to selected residential units. Five core CPTED principles were adapted: natural surveillance, access control, territorial reinforcement, maintenance, and target hardening, all implemented through participatory engagement. The outcomes indicate that CPTED-integrated interior design significantly enhances residents' perception of safety and fosters greater community awareness and active participation in maintaining a secure environment. An interior design sensitive to security aspects serves as both an educational tool and a practical preventive measure. These findings underscore that design interventions at the residential scale yield meaningful social impacts. Applying CPTED at the household level not only improves physical security but also strengthens social cohesion. Therefore, the results of this service project are significant as a replicable model of design-based preventive strategies that can be adopted in other urban communities facing similar challenges.